ANALISIS EFISIENSI USAHA PENGGEMUKAN DOMBA DARI POLA KEMITRAAN ANTARA PERUSAHAAN DENGAN PETERNAK DI JAWA BARAT - Edi Mardiana (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2020)
The performance of sheep breeders in West Java is still low. This can be seen from the decline in the productivity of the sheep business from year to year, namely in 2017 993,087 tons, while in 2018 as many as 857,552 tons. Therefore, to encourage the development of the sheep business, cooperation is pursued through a partnership pattern. This study aims to determine the factors that affect the efficiency of the sheep fattening business, evaluate the level of technicall, allocative, economic efficiency and measure the degree of partnership between companies and breeders. Respondents were determined by survey using the multistage cluster random sampling model, resulting in 10 groups of respondents from a total population of 31 groups. Data collection was carried out in November–Desember 2019, then analyzed using the Cobb-Douglass production function model. The results showed that factors that influenced the production of the sheep fattening business were feeder, forage, area of pen, outpouring of labor, number of dependents and degree of partnership. In general, the business of the sheep fattening is not efficient technically, allocatively and economically. The use of production factors which allocatively need to be reduced is the amount of feeder (0,01677), concentrate (-1,08009), cage area (0,009393), labor outpouring (0,57167) and forage (0,80451). This condition causes the fattening business of the sheep with a technical and economic partnership pattern to be inefficient. However, the implementation of the partnership pattern was relatively good, this condition can be seen with the average score of the degree of partnership pattern of  83,34 percent.